1999
DOI: 10.1007/s004200050391
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal disorders among female dental personnel - clinical examination and a 5-year follow-up study of symptoms

Abstract: Dental personnel had an increased risk of developing musculoskeletal disorders as verified by symptoms and diagnoses and more painful or persistent conditions. This led to a selection out of work. The questionnaire and the present pain rating gave a relatively good picture of the prevalence of musculoskeletal disorders arising from the neck, shoulders, and hips and would be useful as screening tools. Their sensitivity in detecting disorders was higher for diagnoses than for findings. However, these methods wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
150
6
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(184 citation statements)
references
References 23 publications
14
150
6
3
Order By: Relevance
“…of respondents, %) Neck 70 (18) 14 (16) 9 (11) 13 (28) 18 (21) 16 (18) Upper back 77 (20) 14 (16) 8 (10) 12 (26) 25 (30) 18 (21) Lower back 85 (22) 17 (19) 13 (16) 11 (24) 24 (29) 20 (23) undergraduate dental students. The reported prevalence of musculoskeletal pain in this study (79%) is in line with similar studies for both dentists, ranging from 64%-93%, 1,5,11,12 and dental students, ranging from 46%-86%. [13][14][15] Rising et al 13 reported that there was a significant year-by-year increase of a perception that dental procedures aggravate musculoskeletal pain amongst dental students from California.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…of respondents, %) Neck 70 (18) 14 (16) 9 (11) 13 (28) 18 (21) 16 (18) Upper back 77 (20) 14 (16) 8 (10) 12 (26) 25 (30) 18 (21) Lower back 85 (22) 17 (19) 13 (16) 11 (24) 24 (29) 20 (23) undergraduate dental students. The reported prevalence of musculoskeletal pain in this study (79%) is in line with similar studies for both dentists, ranging from 64%-93%, 1,5,11,12 and dental students, ranging from 46%-86%. [13][14][15] Rising et al 13 reported that there was a significant year-by-year increase of a perception that dental procedures aggravate musculoskeletal pain amongst dental students from California.…”
Section: Discussionsupporting
confidence: 91%
“…[15][16][17] As participants of this study provided self-reported information there is the potential for bias, and it could be suggested that more accurate results could be obtained by using physical examinations and assessments. 12 However, these may be limited to assessment of posture, functional movement or asymmetry, which may not reflect the day-to-day impact of these problems. Alternatives would be the use of established scales that record functional or daily living impairment, such as the Roland-Morris scale for back pain and disability 18,19 or the Neck Disability Index.…”
Section: Discussionmentioning
confidence: 99%
“…Although not reported in the results section, these values are comparable to values found in the present study with sensitivity ranging 33-70 % and specificity ranging 75-94 %. Akesson et al (1999) found the sensitivity for the neck/shoulder to be higher than for the elbows/hands/wrists, but this could not be confirmed by the data of the present study. A high correlation between selfreported neck/shoulder symptoms and clinical signs of a neck/shoulder disorder was observed in a cohort of 243 Fig.…”
Section: Validity Of Using Questionnaires For Assessment Of Musculoskcontrasting
confidence: 99%
“…This is in contrast to several other studies that reported higher prevalences for questionnaires compared to physical examinations (Zetterberg et al 1997;Nordander et al 1999;Toomingas et al 1995;Bjorksten et al 1999;Salerno et al 2000). Other studies report sensitivities of 52-60 % (Stål et al 1997), 97 % for the neck and shoulders (Bjorksten et al 1999) and 50-89 % (Akesson et al 1999), and specificities of 86-98, 41 and 55-89 %, respectively. Although not reported in the results section, these values are comparable to values found in the present study with sensitivity ranging 33-70 % and specificity ranging 75-94 %.…”
Section: Validity Of Using Questionnaires For Assessment Of Musculoskcontrasting
confidence: 56%
See 1 more Smart Citation